The Great Depression and the rise of female employment: A new hypothesis - Andriana Bellou; Emanuela Cardia (University of Waterloo, Canadian Labour Economics Forum (CLEF), 2020)
The life-cycle labor supply of women born at the turn of the 20th century diverged sharply from previous cohorts. Although they had similar participation rates in early adulthood, younger cohorts were significantly more likely to work at middle age. This paper documents a link between these changing patterns of female labor supply and the Great Depression. We find that the onset of the Great Depression led to a large increase in young women's labor force participation in 1930 via an added-worker effect. Cohorts induced into the workforce in the early 1930s had significantly higher employment rates through the 1940s and 1950s, suggesting a permanent impact of the Great Depression on women's lifecycle labor supply.
Keywords: 330; Wirtschaftskrise; Weibliche Arbeitskräfte